Physiologically Based Pharmacokinetic (PBPK) Simulation of Supratherapeutic Meropenem Exposure and Potential Pharmacokinetics/Pharmacodynamics (PK/PD) Discordance in a Critically Ill Pediatric Patient: A Case Report - Andika Yusuf Ramadhan (PT Dexa Medica, 2026)
Background: Meropenem is widely used in critically ill pediatric patients; however, sepsis and renal impairment can markedly alter its pharmacokinetics profile, increasing the risk of drug accumulation. Furthermore, therapeutic drugmonitoring is not readily available in many clinical settings. Case presentation: A 6-year-old child (body weight 18.6 kg, height 102 cm) presented with severe pneumonia and sepsis complicated by acute kidney injury. Laboratory findings showed elevated serum creatinine (1.9 mg/dl), reduced estimated glomerular filtration rate (eGFR)(22.17 ml/minute/1.73 m²), mild hypoalbuminemia (3.2 g/dl), and elevated transaminase levels (AST 67 U/l, ALT 89 U/l). Intravenous meropenem was administered, and a physiologically based pharmacokinetic (PBPK) model was utilized toassess and predict drug exposure. Methods: PBPK simulations were performed using PK-Sim®, incorporating pediatric physiology, impaired renal clearance, low protein binding, and drug-specific physicochemical properties. Results: The model predicted marked meropenem accumulation following repeated dosing. The predicted plasma concentration at 0.5 hours postdose (C0.5) was 69.82 mcg/ml. After the fourth dose, the predicted peak concentration (Cmax) reached 183.42 mcg/ml, while the trough concentration (Ctrough) remained elevated at 139.94 mcg/ml. Free drug concentrations remained above the minimum inhibitory concentration (MIC) throughout the dosing interval, resulting in 100% fT>MIC.Supratherapeutic concentrations caused by altered PK/PD may lead to neurotoxicity in critically ill children, whereas even therapeutic dosing may result in microbiome alterations. Conclusion: This case demonstrates that standard meropenemdosing in critically ill pediatric patients with renal impairment may lead to supratherapeutic exposure despite full pharmacodynamic target attainment. PBPK modeling may help anticipate exposure extremes and support individualized dosing when renal function is unstable and therapeutic drug monitoring is unavailable.